Strategic Choice Development Using SWOT Analysis: Diversification Strategy of Batik Creative Industry in Blora, Indonesia - Widjajanti, Kesi; Sugiyanto, Eviatiwi Kusumaningtyas; Widyaevan, Dea Aulia; Sari, Anisa Rachma (Universitas Negeri Semarang, 2023)
Diversification is a strategic choice to improve company competitiveness sustainably. This paper explores strategies and suggests a suitable diversification strategy for micro, small, and medium enterprises (MSME) on a theoretical concentration and resource-based view.. Blora batik creative industry in Central Java, Indonesia, is selected as a case study. We use descriptive analytic derived from quantitative SWOT framework by combining matrix from Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS). We collect data from field surveys and study literature. Respondents are selected purposively based on a result from a focus group discussion (FGD). This paper finds that Blora batik has both positive IFAS and EFAS scores, 0.42 and 0,26, respectively. These indicate Blora Batik has a strong positional value in